Colonial government 1776 1906---England's government of American colonies vs. United States' government of Philippines - Meyer, Ella M. (My University, 1907)
Introduction: Since the United States has gained control of the Philippine Islands and has entered upon a colonial career, many questions have arisen concerning her colonial policy. One of the questions which, prehaps, has not been discussed as frequently as those pertaining to the constitutional rights of the United States to own and govern colonies, is the question: "Are they governing the Philippine Islands according to their ideals of colonial government in I776?" They then formed their ideals from the view-point of the colonies; they now can see the fitness of those ideals when viewed from the standpoint of the Mother country. The revolutionary war was fought because they objected to the way England governed her American colonies. Are they governing the Philippine Islands as they wished to be governed in 1776; or are they governing them more nearly as England governed?
Citation: Meyer, Ella M. Colonial government 1776 1906---England's government of American colonies vs. United States' government of Philippines. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: The Philippines; The United States's role in The Philippines; Colonialism; Theses